Flavour identification in frontotemporal lobar degeneration. Issue 1 (8th November 2012) - Omar, Rohani; Mahoney, Colin J; Buckley, Aisling H; Warren, Jason D
Abstract : Background: Deficits of flavour processing may be clinically important in frontotemporal lobar degeneration (FTLD). Objective: To examine flavour processing in FTLD. Methods: We studied flavour identification prospectively in 25 patients with FTLD (12 with behavioural variant frontotemporal dementia (bvFTD), eight with semantic variant primary progressive aphasia (svPPA), five with non-fluent variant primary progressive aphasia (nfvPPA)) and 17 healthy control subjects, using a new test based on cross-modal matching of flavours to words and pictures. All subjects completed a general neuropsychological assessment, and odour identification was also assessed using a modified University of Pennsylvania Smell Identification Test. Brain MRI volumes from the patient cohort were analysed using voxel-based morphometry to identify regional grey matter associations of flavour identification. Results: Relative to the healthy control group, the bvFTD and svPPA subgroups showed significant (p<0.05) deficits of flavour identification and all three FTLD subgroups showed deficits of odour identification. Flavour identification performance did not differ significantly between the FTLD syndromic subgroups. Flavour identification performance in the combined FTLD cohort was significantly (p<0.05 after multiple comparisons correction) associated with grey matter volume in the left entorhinal cortex, hippocampus, parahippocampal gyrus and temporal pole. Conclusions: Certain FTLD syndromes are associated with impaired flavour identification and this is underpinned by grey matter atrophy in an anteromedial temporal lobe network. These findings may have implications for our understanding of abnormal eating behaviour in these diseases.